2021
DOI: 10.1116/6.0001180
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-free transport of samples in silane-doped inert gas atmospheres for surface analysis

Abstract: We report on a new approach to transport samples for surface analysis safely from oxidation over long distances. The transport method is based on silane-doped inert gases, which are used as a transport medium. In this paper, we show that with the help of silane, highly purified inert gas atmospheres with oxygen contents of less than 10−15 mbar can be generated. In addition, we demonstrate that compared to commercially available inert gases, silane-doped inert gas atmospheres can be efficiently used to store an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 22 publications
0
11
1
Order By: Relevance
“…As shown in Figure S13, the adsorbed O 2 molecule can spontaneously decompose into two O atoms on the surface. In the experiment, this issue can be addressed using an inert gas. , In addition, there are various ways of protecting the electrode materials. For example, although pure lithium metal can be very easily oxidized, with protection, it can still be used as the electrode in lithium metal batteries.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure S13, the adsorbed O 2 molecule can spontaneously decompose into two O atoms on the surface. In the experiment, this issue can be addressed using an inert gas. , In addition, there are various ways of protecting the electrode materials. For example, although pure lithium metal can be very easily oxidized, with protection, it can still be used as the electrode in lithium metal batteries.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, the used oxygen sensor is a lambda probe known from exhaust gas analysis in combustion engines (Mesa GmbH, Germany) and suitable for trace oxygen measurements as previously shown in the literature. , The used lambda probe is based on a heated solid zirconia ceramic electrolyte ( T = 873 K) covered by a porous platinum layer, and a porous ceramic layer for the analyte site, respectively. The working principle is described in detail elsewhere. , According to the Nernst equation (eq ), the oxygen partial pressure of the analyte normalp normalO 2 normala normaln normala normall normaly normalt normale can be expressed by a reference pressure ( normalp normalO 2 normalr normale normalf normale normalr normale normaln normalc normale ), the Faraday constant F , the product of the universal gas constant and temperature RT , and the measured cell voltage U λ .…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, it was shown that the deoxidation of steel during high temperature brazing in a SiH 4 -doped argon atmosphere (with SiH 4 concentrations from 1 to 100 ppm) showed an enhancement in the deoxidation performance in comparison to the processes in pure Ar or N 2 gases [15]. The gain in deoxidation performance was also linked with an elimination of residual oxygen in the amount of several ppm, which is usually present in inert gases [15][16][17][18]. Nevertheless, besides a deoxidation effect, a generation of contaminations like SiO 2 particles as a reaction product was observed [15].…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, the usage of SiH 4 -doped argon or nitrogen gases in different industrial processes is expected to provide considerable improvement of the manufacturing operations in comparison to pure gases, which is mainly connected with a creation of better protective atmospheres with less amounts of oxygen [15][16][17][18]. The high oxygen affinity of silane allowed to significantly decrease the oxygen partial pressure to less than 10 -15 hPa, therefore providing an oxygen-free environment and preventing possible re-oxidation of the material [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation